Investigating slope stability of multiple stopes prone to instability in the Ziluoyi iron ore mining site - Zhongao Yang; Ziling Song; Xiaohua Ding; Mvondo Nga Michele Victoire; Ali Moussa Abdoul Wahab; Barry Oumar; Fanghui Yang; Abdullahi Yusuf Ibrahim; Zhen Gao; Zhaoxi Long (Scientific Reports)
Abstract The ore mining sites commonly experience slope instability, which is causing concern for the workers’ safety and the operation’s stability. Considering the Ziluoyi iron ore mining site as a case study, uniaxial compression strength and shear tests are performed on the lower disk peripheral rock, ore body, and upper disk peripheral rock, leading to the extraction of compressive strength and elastic modulus (lower disk: 77.7 MPa–9.093 GPa; ore body: 19.6 MPa–4.619 GPa; upper disk: 55.47 MPa–5.573 GPa). Further, using the Hoek–Brown criterion in conjunction with the Moher–Columb criterion, the cohesion and internal friction angle of various samples are appropriately determined (lower disk: 21.124 MPa–35.614°; ore body: 21.66 MPa–26.5°; upper disk: 42.916 MPa–25.743°). By employing an appropriate rock mass reduction model, its constants (m and s) and RMR score for the consisting layers (schist layer and ore body) of the three understudy slopes (Slope#1–Slope#3) are evaluated. An effective algorithm based on the Morgenstern–Price method is employed and its effectiveness is also proved by comparing its factor of safety results with those of Geo-Slope for various slope structures subjected to different loads. Subsequently, the stability analyses of various slopes are methodically examined by predicting the factor of safety values under multiple types of loading (i.e., self-weight + groundwater, slope self-weight + groundwater + blasting vibration force, and self-weight + groundwater + seismic force). The factor of safety values of the slopes pertinent to Slope#1/Slope#2/Slope#3 subjected to the above loading conditions are obtained as 1.354/1.273/1.188, 1.326/1.239/1.169, and 1.321/1.232/1.162, respectively. Upon comparing these results with those of a valid homeland specification, it becomes clear that the results are able to meet safety standards and ensure efficient mine operation.